Million Dollar Plants and Retail Prices - Bhardwaj, Abhishek (World Bank, Washington, DC, 2022)
This paper studies how the opening of a Million Dollar Plant (MDP) affects income inequality, by focusing on a new mechanism: retail inflation. Using detailed barcode-level prices, the paper shows that local barcode-level prices increased in winning counties compared to runner up counties after a MDP enters. The paper further shows that households in winning counties spend less time shopping for deals and discounts and more time on work. Wages also go up in winning counties, but only for high-skilled workers. The paper builds a model of monopolistic firms with variable mark-ups and non-homothetic consumer preferences. Consumers become less price sensitive as they substitute shopping time for more working time in response to rising labor demand generated by the entry of a MDP, and firms respond to less elastic consumer demand by raising their mark-ups. Analysis using the model and detailed reduced form evidence shows that establishing a MDP only increases wages of certain high-skilled workers, but it increases overall county-level prices, thus creating larger increases in income inequality in winning counties compared to runner-up counties.